2018
DOI: 10.7567/jjap.57.080307
|View full text |Cite
|
Sign up to set email alerts
|

Raman stress measurement of crystalline silicon desensitizes shear stress: Only on {001} crystal plane

Abstract: Silicon-based semiconductor materials, especially {001} silicon, are the main functional materials in the electronic information industry. Residual stress plays an important role in the reliability of semiconductor devices. However, the stress state is often simplified, especially when the effect of shear stress on Raman wavenumber is neglected. In this study, the relationship between the Raman wavenumber and the plane stress components of typical crystal planes is established. It is observed that only the Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Comparatively similar results were reported in Si with the same diamond crystal structure; they observed that the effects of shear stress were not so much reflected in the change of the Raman peak position when stress analysis on Si wafers under uniaxial loading was performed . Thus, also in our diamond case, this strongly suggests that shear stress is induced in the four-folded petal region with increases in the Raman peak intensity but with very slight shifts of its peak position, as shown in Figure b,e.…”
Section: Resultssupporting
confidence: 88%
“…Comparatively similar results were reported in Si with the same diamond crystal structure; they observed that the effects of shear stress were not so much reflected in the change of the Raman peak position when stress analysis on Si wafers under uniaxial loading was performed . Thus, also in our diamond case, this strongly suggests that shear stress is induced in the four-folded petal region with increases in the Raman peak intensity but with very slight shifts of its peak position, as shown in Figure b,e.…”
Section: Resultssupporting
confidence: 88%
“…The ability of backscattering micro-Raman to probe the sum of principal stresses in {100} c-Si is well known. Using a characterization model that considered NA, refraction and depolarization as in this paper, or a generic model that did not consider NA, refraction and depolarization [18,37], or even the classical method by de Wolf that ignored the effect of shear stress and simplified stress state [23], it is possible and only possible to characterize the principal stresses sum of {100} c-Si using backscattering micro-Raman. Some papers had theoretically concluded that the use of a large-NA objective lens could excite and collect TO mode information and "could" contribute to the decoupling of stress components from {100} c-Si [30].…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al proved that the backscattering Raman measurement results of {100} c-Si were independent of the shear stress through theoretical derivation and calibration experiments, which is due to the triple degeneracy of the Raman peaks of c-Si. Decoupling analysis of stress components cannot be achieved because the Raman shift is linearly related to the sum of the principal stresses [17,18]. To decouple stress components, Loechelt et al proposed a method for decoupling analysis using off-axis measurement and developed a related device [19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the stiffness tensor C, the strain phonon deformation potential (PDP) tensor K ij (i, j = 1, 2 … 6) is reduced to six nonzero components and can be described as in Equation 6: [33] K =…”
Section: Theoretical Methods To Correlate Mechanical Stress To Variamentioning
confidence: 99%